ZBTB7A promotes migration, invasion and metastasis of human breast cancer cells through NF-κB-induced epithelial–mesenchymal transition in vitro and in vivo - Mao, Anyun; Chen, Maojian; Qin, Qinghong; Liang, Zhijie; Jiang, Wei; Yang, Weiping; Wei, Changyuan (Journal of biochemistry (Tokyo), 2019)
It has been generally confirmed that zinc finger and BTB domain containing 7A (ZBTB7A) plays an important role in the occurrence and progression of malignant tumours, but the promotion or inhibition effect is related to tumour type. The mechanism between ZBTB7A and breast cancer is not well understood, so further research is needed. In this study, we first investigated the expression of ZBTB7A in tissue samples of clinical breast cancer patients, MDA-MB-231, MCF-7 and MCF-10A cells. Second, we overexpressed the ZBTB7A in MCF-7 cells and silenced the ZBTB7A in MDA-MB-231 cells using lentivirus transfection technology, respectively, and verified the effect of ZBTB7A on migration and invasion of breast cancer cell lines through in vitro cell function experiments, such as wound-healing assay, migration and invasion assay, quantitative real time reverse transcriptase (qRT-PCR) and western blot. Then, the correlation between the above influences, epithelial–mesenchymal transition (EMT) and NF-κB was analysed. Finally, in vivo tumour transplantation model in nude mice was established to verified the effect of ZBTB7A on metastasis of breast cancer MDA-MB-231 cells. In conclusion, ZBTB7A is highly expressed in cancer tissue, breast cancer cell line MDA-MB-231 and MCF-7. Meanwhile, the high expression of ZBTB7A may promote cell migration, invasion and tumour metastasis, which may be related to EMT events by regulating NF-κB.